Analisis Rasio Berdasarkan Kepmen BUMN Nomor Kep-100/Mbu/2002 Sebagai Penilaian Tingkat Kesehatan Perusahaan dari Aspek Keuangan : Studi Kasus pada PT Semen Baturaja Tbk tahun 2020-2022 - Gunardi, Gunardi; Aisyah Ramadani, Asih; Wulan Septiani, Dian; Siti Rostiana, Tanti; Ikhsan, Sugiyanto (Universitas Koperasi Indonesia, 2023)
Every company needs information about the health level of its company, to boost productivity and competitiveness including the state-owned companies.. Therefore, the government released BUMN Ministerial Decree Number Kep-100/MBU/2002 which explains the assessment of the health level of BUMN. The aim of this research is to measure the financial health of PT Semen Baturaja Tbk, in accordance with the criteria set out in the Decree of the Minister of BUMN Number Kep-100/MBU/2002 concerning the assessment of the health of BUMN. The method used in this research is the quantitative descriptive method. Financial data is taken from the financial reports of PT Semen Baturaja Tbk from the period 2020 to 2022. The results of the research show that PT Semen Baturaja Tbk in 2020 succeeded in achieving category A with a healty predicate, while in 2021 and 2022 PT Semen Baturaja Tbk received a healthy predicate with achievement in AA category.